Rancang Bangun Sistem Informasi E-Catalogue Berbasis Web Mobile Sebagai Media Informasi Produk pada CV Devindo Multi Wahana - M. Radhi As Shidqie; Farizi Ilham; Deniar Purnama; Rizki Jailani (CV. Shofanah Media Berkah, 2026)
CV Davindo Multi Wahana is a plastic packaging product distributor serving health institutions, MSMEs, and wholesalers. Currently, the process of searching and delivering product information by the sales team still relies on manual records and bookkeeping, as the company does not yet have a physical or digital catalog. This often triggers miscommunication regarding technical specifications (plastic size and thickness), slow updates of fluctuating prices, and difficulties for the sales team in checking stock availability independently while in the field. This study aims to design and build a web-mobile-based E-Catalogue information system to integrate product information presentation systematically. System development was carried out using the Extreme Programming (XP) method with planning, design, coding, and testing stages, and was built using the PHP programming language and MySQL database. Black-Box Testing results show that the system successfully facilitates product search through specification filters, calculates automatic prices, and provides a direct order feature to the admin's WhatsApp, which significantly minimizes human error and accelerates the sales team's workflow.